CD101 Topical Compared With Oral Fluconazole for Acute Vulvovaginal Candidiasis: A Randomized Controlled Trial. Issue 3 (July 2019) - Nyirjesy, Paul; Alessio, Cynthia; Jandourek, Alena; Lee, Jon D.; Sandison, Taylor; Sobel, Jack D.
Abstract : Objectives: Vulvovaginal candidiasis (VVC) is an infection of the vagina's mucous membranes, caused by Candida albicans in more than 90% of acute VVC. Several topical and oral azole agents are available in a variety of formulations, and all seem to have similar effectiveness. Azoles are fungistatic, meaning that the fungi are inhibited from growth or replication but are not eradicated. Recurrent infection and developing azole resistance demonstrate a significant need for alternative treatments. Materials and Methods: One hundred twenty-six women were randomized to 1 of the following 3 treatment cohorts: CD101 3% gel ( n = 50) applied intravaginally on days 1 and 2, CD101 6% ointment ( n = 50) applied intravaginally on day 1, or oral fluconazole 150 mg ( n = 26) on day 1. Primary outcomes of clinical and mycological cure, as demonstrated by changes in the vaginal scores and mycological culture, were assessed on day 7 (±2 days), day 14 (±2 days), and day 28 (±7 days). Safety assessments included treatment-emergent adverse events. Results: Ninety-nine women with positive Candida culture remained in the modified intent-to-treat population with 40 in each CD101 arm and 19 in the fluconazole arm. In the CD101 gel, CD101 ointment, and oral fluconazole groups, 35%, 30%, and 52.6% demonstrated clinical cure and 45%, 40%, and 57.9% had mycological cure at day 28, respectively. Conclusions: CD101 3% gel and CD101 6% ointment were well tolerated and produced similar rates of clinical and mycological cure in patients with an acute, moderate-to-severe episode of VVC. However, cure rates for these 2 formulations and regimens of CD101 were lower than those in patients treated with fluconazole.